The Role of Artificial Intelligence in Improving Customer Experience in The Global Hospitality Industry - Padri, Abdul Robi; Sumiyati, Sumiyati; Fauziyyah, Ghina; Ridzki, Mohamad Maulana; Sagita, Ahmad Bahar (Politeknik Siber Cerdika Internasional, 2025)
Digital transformation in the hospitality industry has driven the adoption of artificial intelligence (AI) as a strategic tool in improving service quality and customer experience. This research aims to explore how AI technologies, such as chatbots, facial recognition, predictive analytics, and smart room control, are implemented in the context of hotel operations and their impact on guest perception and satisfaction. Using a descriptive qualitative approach, data was collected through in-depth interviews with hotel management, questionnaires to licensed employees, as well as direct observation at a leading international hotel. The results show that AI is able to accelerate service processes, improve operational efficiency, and provide personalized experiences that have an impact on increasing customer loyalty. However, the findings also reveal challenges such as lack of employee training, guest resistance to automated services, and ethical issues of data privacy. The implications of this study suggest the need for a hybrid service approach between AI and human labor, as well as stronger education strategies and data protection policies. This research contributes to a comprehensive understanding of the role of AI in the hospitality sector and informs the formulation of customer-oriented technology-based service policies.